2020
DOI: 10.36080/idealis.v3i1.1557
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Metode Analytical Hierarchy Process (Ahp) dan Simple Additive Weighting (Saw) Dengan Model QCDFR Untuk Pemilihan Supplier Terbaik Pada Ud. Bayu Agung Furniture

Abstract: Bayu Agung Furniture adalah perusahaan yang bergerak di bidang produksi mabel dan furniture, dalam oprasionalnya UD.Bayu Agung Furniture membutuhkan supplier untuk memasok bahan baku produksi. Salah satu upaya dalam mendapatkan supplier terbaik dan berkualitas adalah melakukan pemilihan supplier, karena itu pemilihan dalam pemasok bahan baku atau supplier sangat penting dalam perusahaan produksi. Akan tetapi, UD. Bayu Agung Furniture memiliki masalah dalam pengambilan keputusan supplier tersebut sepertitidak b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on research [7], using the VPI framework QCDFR and AHP methods, it was found that the VPI framework QCDFR is more suitable compared to the previous one that only focused on quality, cost, & delivery and quality as the main priority criteria. Based on research [8], using QCDFR as the basis of criteria but not using sub-criteria, which is a drawback of this study, with the result of knowing which suppliers are in line with the company's needs and which are not, thus making it easier for the company to make decisions for the next period.…”
Section: Related Workmentioning
confidence: 99%
“…Based on research [7], using the VPI framework QCDFR and AHP methods, it was found that the VPI framework QCDFR is more suitable compared to the previous one that only focused on quality, cost, & delivery and quality as the main priority criteria. Based on research [8], using QCDFR as the basis of criteria but not using sub-criteria, which is a drawback of this study, with the result of knowing which suppliers are in line with the company's needs and which are not, thus making it easier for the company to make decisions for the next period.…”
Section: Related Workmentioning
confidence: 99%
“…Permasalahan tersebut harus diselesaikan dengan baik. Menurut (Susilo & Mahdiana, 2019) metode yang digunakan pada kasus ini adalah Analytical Hierarchy Process (AHP) dan Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). Metode AHP dipilih agar memudahkan lancarnya persoalan secara struktur suatu hirarki kriteria dan mendapat supplier yang berkualitas dengan kebutuhan perusahaan.…”
Section: Pendahuluanunclassified